Low energy availability in male athletes: A systematic review of incidence, associations and effects - McGuire, A.; Warrington, G.; Doyle, L. (Translational Sports Medicine, 2020)
The Female Athlete Triad has recently been suggested to be a threat to male athletes. This review aims to examine the evidence, and associated effects, of low energy availability (LEA) in male athletes. A comprehensive search of PubMed and SportsDiscus was performed. Three RCT and seven CS studies were included that measured energy availability and included well trained males. Clinical LEA (<30 kcal/kg LBM/ day) or subclinical LEA (36 ± 6 kcal/kg LBM/day) was evident within all CS studies, documenting 25% of middle and long distance runners and race walkers and 70% of cyclists with LEA. Two out of three RCTs and three out of seven CS studies reported disrupted endocrine functioning, particularly reduced testosterone levels, in association with LEA. One CS study reported that up to 40% of cyclists with LEA had low BMD. One CS study assessed metabolic health, reporting those with suppressed levels spent more time in a severe energy deficit. This review highlights that LEA appears prevalent across male athletic populations, in particular endurance and weight class athletes, and is a potentially serious threat to bone, endocrine and metabolic health. Future larger scale longitudinal studies, using appropriate study designs, should be undertaken to confirm these threats.